2022
DOI: 10.1155/2022/5943649
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Efficiency of Medicinal Plants for the Treatment and Prevention of COVID-19

Abstract: The COVID-19 pandemic has once again prompted people to resort to the remedies of folk and alternative medicine. Medicinal plants, because of their chemical composition, pharmacological properties, and the action of biologically active substances, can stop and relieve the symptoms of the disease. The purpose of the work is a comparative flora analysis of medicinal plants to identify the most prospective plant and further production of a remedy for the avoidance, treatment, and rehabilitation of COVID-19. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 111 publications
0
0
0
Order By: Relevance
“…For many individuals, herbal remedies serve as the primary, and sometimes sole, source of medical care, owing to their territorial accessibility and financial feasibility. Moreover, amid the COVID-19 pandemic, the affordability and accessibility of most herbal remedies have amplified their appeal compared to conventional medicines [24] . Fan et al [25] in their review of seven clinical trials involving 736 COVID-19 patients, collectively demonstrated that the use of Chinese herbal medicine as adjunctive therapy alongside standard care improved treatment outcomes in COVID-19 cases.…”
Section: Discussionmentioning
confidence: 99%
“…For many individuals, herbal remedies serve as the primary, and sometimes sole, source of medical care, owing to their territorial accessibility and financial feasibility. Moreover, amid the COVID-19 pandemic, the affordability and accessibility of most herbal remedies have amplified their appeal compared to conventional medicines [24] . Fan et al [25] in their review of seven clinical trials involving 736 COVID-19 patients, collectively demonstrated that the use of Chinese herbal medicine as adjunctive therapy alongside standard care improved treatment outcomes in COVID-19 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Spices and herbs that are sources of natural antioxidants, can protect against oxidative stress and thus play preventive role in many diseases [13]. The medicinal properties of folk plants are mainly attributed to the presence of flavonoids, other organic, and inorganic compounds such as coumarins, phenolic acids, and antioxidant micronutrients and are able to counter various metabolic disorders, cancers, and COVID-19 [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Однако ряд растений из этномедицинских баз данных находятся в лабораторных условиях по всему миру, среди которых и растения рода Filipendula. Из приведенных выше данных можно сделать вывод, что экстракты из растений рода Filipendula обладают интересными противовоспалительными свойствами, которые представляют большой потенциал для терапевтической практики человека [40] и при том не только в сфере иммуномодулирующего действия. Салицилаты не являются единственными интересными соединениями в этих растениях, наличие аскорбиновой кислоты способствует общеукрепляющему действию на организм.…”
unclassified